Analisis Keefektifan Kalimat pada Teks Opini dalam Website Liputan6.com Edisi Februari 2025 sebagai Bahan Bacaan dan Sumber Informasi bagi Mahasiswa - Viyasqi Arsy Putri; Muhammad Rizal Almajid; Meidika Dendra Parameswara; Maulana Adi Saputra; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Riyadi Widhiyanto (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study analyzes the quality of content and the ineffectiveness of sentences in opinion texts found on the "Liputan6.com" website in February 2025 as reading material and sources of information for students. This study uses descriptive qualitative research methods and a syntactic approach. Qualitative research and syntactic approaches are used to analyze the quality of content and effective sentences. The research data is the result of identifying ineffective sentences used in opinion texts on the "Liputan6.com" website, February 2025 Edition as reading material and a source of information for students. The data collection technique in this study uses a syntactic approach in the form of listening and note-taking techniques. In this study, data presentation was carried out using informal methods. The data is presented in a table containing several ineffective sentences and their corrections. The results of the analysis of opinion texts found on the February 2025 edition of the "Liputan6.com" website found 263 structured sentences, consisting of 140 effective sentences and 133 ineffective sentences. From this study, ineffective sentences are classified into 5 categories, namely 14 ineffective sentences due to excessive use of words, 19 due to inappropriate word choice, 12 due to use of foreign languages, 5 due to inappropriate use of conjunctions, 9 due to illogical sentences, 6 due to incorrect use of punctuation, 3 due to use of sentences that are too simple. This study can help writers pay attention to how they write opinion texts that are in accordance with linguistic rules and are useful as a guideline for writing effective sentences.